Faktor Risiko Dispepsia pada Mahasiswa Institut Pertanian Bogor (IPB) - Susanti, Andri; Briawan, Dodik; Uripi, Vera (Jurnal Kedokteran Indonesia, 2011)
Background: Dyspepsia syndrome frequently occurs among adolescents. This study aimed, to analyzerisk factors of dyspepsia among university students.Methods: The study design was a case-control study, where two groups of samples were selectedpurposively in the first grade student living in IPBâs dormitory. The case group was the students withgastric disorder (gastritis or peptic ulcer history) in the last six months, meanwhile the control groupwas having similar characteristics except they suffered gastric disorder. The total of 120 universitystudents were taken pairly as samples, consisting of 60 students for the each group (24 male and 36female). Data were collected include gastric disorder history, dyspepsia symptom, characteristic ofsamples, nutritional status, eating habit, smoking, alcohol consumption, physical activity, drugsconsumption (especially antacid), stress, blood type, and family disease history of gastritis or pepticulcer.Results: The frequency of dyspepsia in the case group was higher than the control group (p<0.05).Gastric disorder history significabtly related to frequency of dyspepsia (p<0.05). The body mass index(BMI) scores of samples had no difference in both sample groups (p<0.05). Having meal regularly,meal frequency, carbonated drink consumption habit, and fat intake related significantly with frequencyof dyspepsia (p<0.05). Physical activity, taking antacid, and stress level related significantly withfrequency of dyspepsia (p<0.05). Family disease history and blood type had no relation with frequencyof dyspepsia. The multiple logistic regression analysis showed that the significant risk factors of dyspepsiaare meal frequency more than twice per day (OR=0.08; CI 95%: 0.02 hingga 0.45), habitually consumecarbonated drink (OR=8.95; CI 95%: 1.27 hingga 63.23), and higher stress level (OR=1.22; CI 95%: 1.06hingga 1.37).Conclusion: Eating frequency more than twice per day can reduce risk of dyspepsia, meanwhileconsuming carbonated drink more than three bottles per week, and having higher stress level preciselyincrease the risk of dyspepsia.Keywords: risk factors, dyspepsia, university students.